Programmable Logic Controller Analog Input Learning Module: An Expert-Based Evaluation - Wati, Miladiah Setio; Maryadi, Totok Heru Tri; Badarudin, Rohjai; Al Hakim, Vando Gusti (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2025)
This study aims to validate the analog input learning module of programmable logic controller (PLC). This module was developed using the OMRON CP1H PLC type which has analog input and analog output configurations. Scientific studies on the quality standards of learning modules are the basis for the development of this instrument. The content validity test was carried out by evaluation experts, while media and material experts evaluated the printed media and PLC material aspects. The results of the study showed an assessment of the media side with an average score of the format aspect of 14.5, the organizational aspect of 27.5, the shape and size of the letters of 13.0, and the consistency aspect of 29.5 which was categorized as "Very Eligible", while the average score of the attractiveness aspect was 22.0 and the space aspect of 12.5 was categorized as "Eligible". The assessment results from the material side with an average score of the self-instruction aspect of 57.0, the adaptive aspect of 6.5, and the user-friendly aspect of 14.0 which is categorized as "Very feasible", while the average score of the self-contained aspect of 13.5 and the stand-alone aspect of 6.5 is categorized as "Eligible". This module is considered feasible for learning PLC analog input with satisfactory assessment results.